2022
DOI: 10.1021/acs.jafc.1c07033
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Nitrogen Rate and Increasing Plant Density Accomplished High Yields with Satisfied Grain Quality of Soft Wheat via Modifying the Free Amino Acid Supply and Storage Protein Gene Expression

Abstract: In a 2 yr field experiment, we investigated the combined effects of reduced nitrogen (N) rate and increased plant density on the trade-off between the grain protein content (GPC) and the grain yield (GY) in soft wheat cultivars. Reducing N application significantly decreased both GPC and GY; however, to some extent, increasing the top-dressed N ratio and plant density compensated for the GY loss. Optimizing the combination of these three factors (150 kg N ha–1 with 50% top-dressed N and 360 × 104 plants ha–1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
1
8
1
Order By: Relevance
“…In agreement with these reports, we observed increased GPC and wet gluten content, a higher Gli/Glu ratio, and a negative correlation between DST and the Gli/Glu ratio in response to higher N rates. Here, a large discrepancy was found between our result and those of Yang et al and Zheng et al, who found that the protein quality index increased as the N application rate increased from 0 kg to an optimum rate under different experiment conditions. In our experiment, the DST and R max decreased when the N rate increased from 100 to 200 kg ha –1 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In agreement with these reports, we observed increased GPC and wet gluten content, a higher Gli/Glu ratio, and a negative correlation between DST and the Gli/Glu ratio in response to higher N rates. Here, a large discrepancy was found between our result and those of Yang et al and Zheng et al, who found that the protein quality index increased as the N application rate increased from 0 kg to an optimum rate under different experiment conditions. In our experiment, the DST and R max decreased when the N rate increased from 100 to 200 kg ha –1 .…”
Section: Discussioncontrasting
confidence: 99%
“…We studied GY5766, which is a bread wheat cultivar, whereas Yang et al . and Zheng et al studied soft wheat cultivars. Additionally, the content of available N in the soil before sowing was much higher in our study (on an average 126.0 mg kg –1 ) than that (on an average 76.4 mg kg –1 ) in the study of Zheng et al…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent conclusions have been made in different studies of fertilization (especially N fertilizer) for weak-gluten wheat [ 13 , 14 , 15 ]. Under 150 Kg N ha −1 with 50% top-dressed N and 360 × 10 4 plantsha −1 , the grain yield loss of soft wheat can be compensated, while PC can be decreased (Zheng et al 2022) [ 7 ]. The result of the fertilization mode might be attributed to the downregulation of high-molecular-weight genes and low-molecular-weight genes in mature grains [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The production of Chinese cookies from weak-gluten wheat has been predicted to dramatically increase from 1.05 million tons in 2004 to 14.4 million tons in 2024. Nevertheless, no more than 1.0% of the total weak-gluten wheat grain production can meet the requirement of cookie making for quality [ 6 , 7 ]. PC and WGC of flour are major parameters to evaluate the quality of wheat for special use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation